KEPUASAN KERJA, KOMITMEN ORGANISASI DAN KEINGINAN BERPINDAH: STUDI PADA KARYAWAN PAHALA EXPRESS JATIASIH BEKASI - Sandra Purbasari Hasbie; Roni Faslah; Darma Rika Swaramarinda (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2016)
The study aims to determine whether there is the influence of job satisfaction and organization commitment towards turnover intention of employess on Pahala Express Jatiasih Bekasi. The study was conducted for 3 (three) months since Januari 2015 until April 2015. The research method is survey method with the correlational approach.. The sample is 119 people, 5% of the population. The sampling technique with proportional random technique.